2018
DOI: 10.1002/jcla.22610
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype‐based association of Vascular Endothelial Growth Factor gene polymorphisms with urothelial bladder cancer risk in Tunisian population

Abstract: CIC haplotype of VEGF gene may be important risk factor for UBC development in Tunisia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…With no obvious correlation identified in hospital‐based studies for allelic contrast (OR = 0.96; 95% CI = 0.69‐1.34; P = 0.813), homozygote comparison (OR = 1.35; 95% CI = 0.94‐1.92; P = 0.101), dominant genetic model (OR = 0.93; 95% CI = 0.61‐1.41; P = 0.730), and recessive genetic model (OR = 1.37; 95% CI = 0.97‐1.95; P = 0.078). Furthermore, we removed two studies that were inconsistent with HWE and also identified similar results (Table b). Notable association between VEGF gene rs3025039C/T polymorphism and BCa risk were observed in Asian descendants under four genetic models (allelic contrast: raw OR = 1.19; 95% CI = 1.05‐1.34; P = 0.006; homozygote comparison: raw OR = 1.54; 95% CI = 1.12‐2.12; P = 0.008; dominant genetic model: raw OR = 1.18; 95% CI = 1.02‐1.36; P = 0.027; and recessive genetic model: raw OR = 1.47; 95% CI = 1.07‐2.01; P = 0.016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With no obvious correlation identified in hospital‐based studies for allelic contrast (OR = 0.96; 95% CI = 0.69‐1.34; P = 0.813), homozygote comparison (OR = 1.35; 95% CI = 0.94‐1.92; P = 0.101), dominant genetic model (OR = 0.93; 95% CI = 0.61‐1.41; P = 0.730), and recessive genetic model (OR = 1.37; 95% CI = 0.97‐1.95; P = 0.078). Furthermore, we removed two studies that were inconsistent with HWE and also identified similar results (Table b). Notable association between VEGF gene rs3025039C/T polymorphism and BCa risk were observed in Asian descendants under four genetic models (allelic contrast: raw OR = 1.19; 95% CI = 1.05‐1.34; P = 0.006; homozygote comparison: raw OR = 1.54; 95% CI = 1.12‐2.12; P = 0.008; dominant genetic model: raw OR = 1.18; 95% CI = 1.02‐1.36; P = 0.027; and recessive genetic model: raw OR = 1.47; 95% CI = 1.07‐2.01; P = 0.016).…”
Section: Resultsmentioning
confidence: 99%
“…37 Previous studies have been carried out to demonstrate the association between VEGF gene polymorphisms and BCa risk, but with inconsistent results. [24][25][26][27] Garcı´a-Closas et al 27 indicated that VEGF gene rs833052 variant was associated with increased risk for BCa (OR = 2.52; 95% CI = 1.06-5.97) based on Spanish population, with no positive correlation observed for rs3025039 polymorphism (OR = 1.63; 95% CI = 0.73-3.61). Fu et al 25 found that both of these two variants were significantly associated with BCa susceptibility in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations